On (T 2 T 3)-Zakharov-Shabat Equations of Generalized Kadomtsev-Petviashvili Hierarchies - Reyes-Garcia, E (American Institute of Physics, 2022)
We review the integration of the Kadomtsev-Petviashvili (KP) hierarchy in several non-standard contexts. Specifically, we consider KP in the following associative differential algebras: an algebra equipped with a nilpotent derivation, an algebra of functions equipped with a derivation that generalizes the gradient operator, an algebra of quaternion-valued functions, a differential Lie algebra, an algebra of polynomials equipped with the Pincherle differential, and a Moyal algebra. In all these cases, we can formulate and solve the Cauchy problem of the KP hierarchy. In addition, in each of these cases, we derive different Zakharov-Shabat (t2, t3)-equations - that is, different Kadomtsev-Petviashvili equations - and we prove the existence of solutions arising from solutions to the corresponding KP hierarchy. © 2022 Author(s).